Effectiveness of Fogging With Spatial Analysis in The Working Area of The East Bogor Health Center - Ratna Dwi Lestari; Budi Utomo (JOURNAL OF BAJA HEALTH SCIENCE, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease transmitted by the Aedes aegypti mosquito. DHF is a frightening disease because its transmission can take place quickly in an area. Even in one month, the number of dengue cases in endemic areas can reach tens of people infected with dengue virus. Maximizing the DHF control program at the local health office and puskesmas is the main key in tackling the spread of DHF. However, it is a current obstacle that has made the DHF control program ineffective in Bogor City, namely the absence of scientific predictions about the location of DHF vulnerable areas in Bogor City, including in the working area of the East Bogor Health Center. So that DHF control programs such as fogging have not been able to significantly reduce DHF cases. This study used observational analysis with a cross-sectional design. The data collected was then analyzed using spatial analysis with the buffer method. The results showed that DHF cases were almost spread throughout the working area of the East Bogor Health Center. Based on interviews with puskesmas officers, the fogging radius is around 200 meters from the fogging location. After carrying out a spatial analysis using the buffer method, it was found that the fogging radius only reached a small part of the East Bogor Health Center work area which was indicated to be a DHF-prone area. Implementation of fogging programs that are not based on DHF vulnerable areas results in ineffective prevention of DHF. Therefore, spatial-based DHF mapping is needed to identify areas that are vulnerable to DHF so that it can be used as a reference in determining fogging locations.